ZNACZENIE NOWELIZACJI USTAWY O INFORMATYZACJI DLA POSTĘPOWANIA PRZED SĄDAMI ADMINISTRACYJNYMI - Chromicka, Dorota (Zeszyty Prawnicze, 2017)
The Importance of the Projected Amendment of the Polish Act on Informatization to the Act on Administrative Court Proceedings Summary Most of the regulations of the polish Act on Informatization of public tasks performed by public organizations passed on 17 February 2005 came into force on 21 July 2005. After almost 4 years some institutions proved to be unsuccessful or did not work as intended. Also fast development of new technologies required amendment of the Act. On 17th June 2009 Governmental project on amendment of the Act on Informatization of pubic tasks performed by public organizations, Administrative Proceedings Code, Tax Ordinance Act and some other acts was sent to Sejm Marshall. Administrative Proceedings Code unlike the Act on Administrative Court Proceedings accepts electronic documents that are electronically signed. Pursuant to Art. 5 section 2 polish Act on Electronic Signature and Art. 78 § 2 Civil Code, qualified electronic signature equals to autograph signature. This confuses parties who have problems with understanding why their pleadings signed with qualified electronic signatures are not accepted by the administrative court. Act on Informatization does not apply on administrative courts now but the project on Amendment of the Act on Informatization passed on 8 January 2010 would oblige them to accept electronic documents in litigation. The Article presents how exactly administrative courts justify not accepting electronic documents now and how it would change when the Amendment of the Act should come into force. Apart from characterizing Supreme Administrative Court’s rulings, this article concentrates on the influence of the Amendment of the Act on Informatization over the Act on Administrative Court Proceedings.